2020
DOI: 10.5194/egqsj-69-93-2020
|View full text |Cite
|
Sign up to set email alerts
|

Der späteiszeitliche Tüttensee-Komplex als Ergebnis der Abschmelzgeschichte am Ostrand des Chiemsee-Gletschers und sein Bezug zum „Chiemgau Impakt“ (Landkreis Traunstein, Oberbayern)

Abstract: Abstract. Anhand von sedimentologischen und geländemorphologischen Untersuchungen wird die Abschmelzgeschichte des südöstlichen Chiemsee-Gletschers beschrieben. Mit dem Trockenfallen der Bad Adelholzen-Erlstätter Rinne im Verlaufe des Spätwürm entwickelt sich aus dem Abschmelzen des Eislappens in der Grabenstätter Bucht eine sich ständig tiefer legende konzentrische Abfolge von zunächst peripheren Entwässerungsrinnen, wobei die ältesten Rinnen dieser Phase bei Chieming, die jüngeren dann entsprechend weiter im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…From a glaciological point of view, the hollow of Tüttensee is related to dead ice which was cut off from the Inn-Chiemsee glacier during the ice decay after the Last Glacial Maximum (LGM) (e.g. Ganss, 1977;Doppler and Geiss, 2005;Huber et al, 2020). Our results support the glaciological explanation because of the following reasons:…”
Section: Lake Level Fluctuations and Climatesupporting
confidence: 72%
See 1 more Smart Citation
“…From a glaciological point of view, the hollow of Tüttensee is related to dead ice which was cut off from the Inn-Chiemsee glacier during the ice decay after the Last Glacial Maximum (LGM) (e.g. Ganss, 1977;Doppler and Geiss, 2005;Huber et al, 2020). Our results support the glaciological explanation because of the following reasons:…”
Section: Lake Level Fluctuations and Climatesupporting
confidence: 72%
“…Recent detailed glacial morphological studies concluded, that Tüttensee did not originate as an impact crater of a meteorite (Huber et al, 2020). Our investigations also contradict clearly the meteorite hypothesis: we found a complete and undisturbed sediment sequence covering the late Würmian and Holocene without any hints of big fires documented by charcoal concentrations in the Iron Age.…”
Section: Study Areasupporting
confidence: 61%
“…The strewn field would form an ellipse elongated from northeast to southwest. The Chiemgau Impact theory, however, is highly controversial, as shown mainly in the discussions about the origin of the lake Tüttensee (near Grabenstätt) and a potential impact into the Lake Chiemsee (see [20][21][22] and references therein). Nevertheless, the discussion of relatively large, water-filled or buried potential impact craters in the region, as well as discussion of the whole Chiemgau Impact theory is beyond the scope of our paper.…”
Section: Craters At Emmerting and Potential Crater At Grabenstätt-kal...mentioning
confidence: 99%